2013
DOI: 10.1542/peds.2012-1220
|View full text |Cite
|
Sign up to set email alerts
|

Complementary and Alternative Medicine Use by Pediatric Specialty Outpatients

Abstract: OBJECTIVE: Complementary and alternative medicine (CAM) use is high among children and youth with chronic illnesses. The objective of this study was to assess the prevalence and patterns of CAM use in 10 subspecialty clinics in Canada and to compare CAM use between 2 geographically diverse locations. METHODS: This survey was carried out at 1 Children’s Hospital in western Canada (Edmonton) and 1 Children’s Hospital in central… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
63
6
5

Year Published

2014
2014
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 96 publications
(79 citation statements)
references
References 34 publications
5
63
6
5
Order By: Relevance
“…Moreover, surveyed respondents may not be able to judge whether a product is an NHP, which may lower the reported frequency of NHP use. The population studied by Adams et al (60) and the children in the present study have chronic conditions; however, our patients had more serious pathology and limited life expectancy. The reasons behind the higher use of NHPs by patients with serious chronic medical conditions may include the lack of hope of achieving full success with conventional medications, or higher rates of side effects experienced due to conventional medications.…”
Section: Discussioncontrasting
confidence: 52%
See 1 more Smart Citation
“…Moreover, surveyed respondents may not be able to judge whether a product is an NHP, which may lower the reported frequency of NHP use. The population studied by Adams et al (60) and the children in the present study have chronic conditions; however, our patients had more serious pathology and limited life expectancy. The reasons behind the higher use of NHPs by patients with serious chronic medical conditions may include the lack of hope of achieving full success with conventional medications, or higher rates of side effects experienced due to conventional medications.…”
Section: Discussioncontrasting
confidence: 52%
“…Adams et al (60) found 37% of the paediatric population they studied, which included 979 surveys from the Stollery Children's Hospital (Edmonton, Alberta) and the Children's Hospital of Eastern Ontario (Ottawa), currently used NHPs. We found a higher frequency of NHP use in children admitted to hospice, which may be explained by several factors.…”
Section: Discussionmentioning
confidence: 99%
“…7 Surveys were administered by a research assistant to all patients in clinic waiting rooms between February and July 2007. Children and their families were eligible to participate if they had not previously filled out a survey, could read French or English and the child was under 18 years of age.…”
Section: Cmaj Openmentioning
confidence: 99%
“…Entre las patologías tratadas con cAM que han sido objeto de estudio se encuentran: cáncer de próstata, de tiroides, de mama, enfermedades dermatológicas y enfermedades ginecológicas, entre otras (29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40).…”
Section: Uso De Las Cam En La Medicina Occidentalunclassified
“…Se ha evidenciado que el uso de las cAM es mayor en mujeres, personas con elevado nivel educativo y altos ingresos (41)(42)(43). La introducción de estas terapias en la infancia es reciente, sobre todo en niños con enfermedades crónicas, recurrentes o incurables, en quienes se usan asociadas a los cuidados primarios (29,30). Por otro lado el uso de estas terapias se ha reportado en enfermedades como el asma, hiperactividad y déficit de atención, autismo, cáncer, fibrosis quísti-ca, diabetes, epilepsia, anemia falciforme, enfermedades gastrointestinales, dermatológicas y psiquiátricas (44)(45)(46)(47)(48)(49).…”
Section: Uso De Las Cam En La Medicina Occidentalunclassified